The Existence of Islamic Boarding Schools in Responding to the Challenges of Era 4.0 - Latipah, Euis; Suhartini, Andewi; Ahmad EQ, Nurwadjah (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This research aims to examine the role of pesantren in facing the challenges of the industrial era 4.0. As a traditional educational institution, pesantren has produced Muslim scholars. In addition, pesantren are also able to develop the potential of students to be able to have religious spiritual strength, personality, intelligence, and noble character. The industrial era 4.0 has positive and negative impacts on all sectors of human life, including the education sector. Therefore, researchers want to see the extent of the role of pesantren in overcoming this uncertain phenomenon. This research uses a library research approach, the data obtained is entirely sourced from literature, namely examining literature sources such as articles and other works related to the existence of pesantren and the challenges of pesantren in the 4.0 era. The results of this study conclude that pesantren have an important role in overcoming various problems and the rapid changes that arise in the industrial era 4.0. Strong spiritual values are a fortress from the negative attacks of sophisticated and massive technological advances.  The rapid development of technology will not be a boomerang if it is addressed wisely. Therefore, all Islamic Education Institutions, especially pesantren, must continue to be sensitive to the changing times by continuously developing existing potential through curriculum development programs and literacy habituation patterns without leaving the identity or values of the pesantren.